ANALISIS PENGGUNAAN QUIZIZZ SEBAGAI ALAT EVALUASI PELAJARAN MATEMATIKA DALAM IMPLEMENTASI KURIKULUM MERDEKA DI SD 067259 MEDAN JOHOR - Fitria Rhamadona; Safrida Napitupulu; Sutarini; Tiflatul Husna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the use of Quizizz as an evaluation tool in mathematics learning within the implementation of the Merdeka Curriculum and to describe students' responses to its use. This research used a qualitative descriptive method. The participants were fifth-grade students of SD Negeri 067259 Medan Johor. Data collection techniques included observation, questionnaires, interviews, and documentation. The results showed that the use of Quizizz as an evaluation tool had been implemented well and supported student-centered learning. Students showed positive responses, as indicated by high enthusiasm, increased participation, and improved motivation during evaluation activities. However, there were obstacles related to unequal access to technology among students. Overall, Quizizz is effective as an interactive evaluation tool in mathematics learning in the Merdeka Curriculum.